Computational methods and clinical applications in musculoskeletal imaging : 5th International Workshop, MSKI 2017, held in conjunction with MICCAI 2017, Quebec City, QC, Canada, September 10, 2017, Revised selected papers /: 5th International Workshop, MSKI 2017, held in conjunction with MICCAI 2017, Quebec City, QC, Canada, September 10, 2017, Revised selected papers. (2018) - Unknown
No abstract available